Scandal and Gender in Colonial and Nineteenth-Century Latin America - Introduction - Lipsett-Rivera, Sonya; Undurraga Schüler, Verónica (Anuario de Historia de América Latina, 2024)
Violating the norms of gender frequently provoked scandal. This section presents the connections between scandal and gender by introducing the articles that are included in this special issue. Scandals may not seem worthy of scholarly work, but they provide an entry into the interstices of gender performance and the ways that people disrupted social norms. Scandals have three components: the transgression, its dissemination, and the receptive public. Gossip about individuals was often at the heart of scandals but it was also an important social force that established community values. The news of scandalous conduct was often spread by murmurings but also by pasquines and in later periods, in newspapers. The definition of the word “scandal” has changed over time as have the elements that seem shocking have evolved. In this special issue, the authors show how space of honor such as convents, recogimientos, and the family home could be violated. Institutions such as the Church and the State tried to enforce a gender binary but many cross-dressed for their own amusement in dramas or as a disguise. Single women were often the most vulnerable to accusations of scandalous behavior, but young men also were the target of accusations of vagrancy when they surpassed their families’ tolerance for youthful antics.